Trophic plasticity of mixotrophic corals under contrasting environments - Sturaro, Nicolas; Hsieh, Yunli Eric; Chen, Qi; Wang, Pei‐Ling; Denis, Vianney (Functional ecology, 2021)
Mixotrophic organisms can derive nutrition from both auto‐ and heterotrophy, which allows them to use a variety of trophic pathways to sustain their metabolic demands under variable conditions. Therefore, when facing environmental change, these organisms are expected to demonstrate an intrinsic ability to acclimatize through trophic plasticity. Scleractinian corals are ecologically important mixotrophs, but understanding their trophic plasticity has been impaired by an oversimplification towards inconsistent proxies of coral diet and overlooking intraspecific variability. Here, we applied a Bayesian analysis of carbon and nitrogen stable isotope data to determine the trophic niches of six common species of scleractinian corals and their associated endosymbionts, and combined it with an unsupervised machine learning algorithm to identify trophic behaviours and strategies. We found a variable amount of nutritional plasticity identified by different trophic behaviours within and between mixotrophic corals living under the same environmental conditions. Furthermore, we observed changes in trophic plasticity across environmental conditions. Corals from variable environments had larger host and endosymbiont niches than corals from stable environments. In addition, deeper corals had niches indicating a greater degree of heterotrophy than shallow corals. Collectively, corals exhibited distinct trophic strategies by promoting trophic niche differentiation along the mixotrophic continuum and conspecific individual colonies displayed high trophic variation. Our results provide a foundation to understand how mixotrophic organisms may adjust their nutrition in response to ongoing global environmental change and the consequential modification of benthic assemblages. 摘要 混營性生物可藉由自營和異營的方式獲取營養, 此特性有助於他們在變動的環境中可透過不同的營養途徑來維持自身代謝所需能量, 因此這些物種被預期可以透過營養可塑性這種內在能力來適應環境的變化。 石珊瑚在生態中扮演著重要的混營性生物角色, 但過去研究多半過度簡化珊瑚食性指標, 以及忽視石珊瑚種內變異的重要, 因此侷限了我們對其營養可塑性的理解。 在本篇研究中, 我們使用貝氏分析法來分析碳、氮穩定同位素資料, 以了解六種常見石珊瑚和其共生藻的營養區位, 並結合非監督式機器學習演算法來辨別珊瑚的營養行為和策略。 我們發現, 在相同的環境下, 混營性珊瑚在種間及種內的不同營養行為可以表現出不同程度的營養可塑性。此外, 營養可塑性會隨著環境條件的不同而改變。相比於穩定的環境, 在擾動較大的環境中, 珊瑚及其共生藻有較大的營養區位。另外, 也發現生存在水深較深的珊瑚比淺水區的珊瑚有著較高程度的異營行為。整體而言, 我們推測珊瑚能透過混合營養區位的分化及同種不同個體間表現的高營養變異性來採取不同的食性策略。 本篇研究結果可以幫助我們更進一步理解混營性生物如何調整其食性, 以應對正在發生的全球環境變化和隨之而來底棲群聚的改變。 A free Plain Language Summary can be found within the Supporting Information of this article. A free Plain Language Summary can be found within the Supporting Information of this article.